Peace for Humanity: Principles, Problems and Perspectives of The Future as Seen by Muslims and Christians - Mahmoud Zakzouk (3eMehO RbRhbs; Andreas Bsteh (India Vikas Publishing House Pvt. Ltd., 1996)
Papers presented at the International Christian-Islamic Conference organized by the Institute for Theology of Religions, from March 30 to April 2, 1993 in Vienna.
Keywords: Social Sciences (3GdYdhe GdGLJeGYjIs; Christianity and other religions -- Islam -- Congresses; Islam -- Relations -- Christianity -- Congresses; General